All real numbers so the answer is D
Answer:
A. (x · 60) + (x · 5)
Step-by-step explanation:
Y = -2x + 5 y =3x - 2
Since both equations are equal to 'y' you can set them equal to each other to solve.
-2x + 5 = 3x - 2 Subtract 3x from both sides
-5x + 5 = -2 Subtract 5 from both sides
-5x = -7 Divide -5 on both sides
x = 7/5
Plug 7/5 back in for x and solve for y.
y = -2(7/5) + 5
y = (-14/5) + (25/5)
y = 11/5
(7/5, 11/5) OR (1.4, 2.2)
Answer:
D
Step-by-step explanation:
4X =2 X +6
=>X = 3
Answer:
I think it's y < 3x +1
Step-by-step explanation:
subtract 6x to the right side. that's -2y > -6x - 2. then divide -2 out of y, now you have to flip the sign. Now you have y < 3x + 1